2017
DOI: 10.3762/bjoc.13.122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of alkynyl-substituted camphor derivatives and their use in the preparation of paclitaxel-related compounds

Abstract: Compounds containing two alkyne groups in close vicinity at the rigid skeleton of camphorsulfonamide show unique reactivities when treated with electrophiles or catalytic amounts of platinum(II). The formed product structures depend not only on the reagents used but also on the substituents attached to the triple bonds. Cycloisomerisations with perfect atom economy lead to polycyclic heterocycles that resemble to some extent the AB ring system of paclitaxel. Herein, we present practical synthetic methods for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The proposed mechanism implies the formation of intermediate 205 (Scheme 83). [129][130][131] Sulfonamide reduction under oxidizing conditions in the above camphorsultam derivative 204 b looks even more puzzling! Thus, the reaction with Br 2 initialized another cascade reaction eventually affording the mixture of bisbrominated polycyclic sultims 208 and 209.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…The proposed mechanism implies the formation of intermediate 205 (Scheme 83). [129][130][131] Sulfonamide reduction under oxidizing conditions in the above camphorsultam derivative 204 b looks even more puzzling! Thus, the reaction with Br 2 initialized another cascade reaction eventually affording the mixture of bisbrominated polycyclic sultims 208 and 209.…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…1) that found in the tallowwood tree or Eucalyptus microcorys. Various alkynes possess remarkable biological activity and they have been utilised as drugs, 7,8 for example, the birth control medicine norethynodrel. 9 In addition, it was reported that some of the natural acetylenes i.e.…”
Section: Introductionmentioning
confidence: 99%